Immunoglobulin G N-glycosylation remodeling in viral infections: immunomodulatory roles and potential biomarker implications - Yan, Ruxu; Wang, Chunqing; Zhao, Xuezhen; Wang, Yingjie; Liu, Meng; Shi, Xiaohong; Chen, Hanxiang; Li, Dong (Frontiers in Immunology, 2026)
The glycosylation of Immunoglobulin G (IgG), a complex post-translational modification, is essential for the structure and function of IgG. The varying affinities of different IgG N-glycans for Fcγ receptors can influence inflammatory responses, including antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC), and antibody-dependent cell phagocytosis (ADCP). Existing research indicates a correlation between IgG N-glycosylation and a range of diseases, such as autoimmune disorders, neurologic diseases, and cancer. Persistent and emerging viral infections pose a significant risk to public health, and the elicitation of innate and adaptive immune responses in the host following viral infection is intricately linked to inflammatory mediators, yet the relationship between viral infections and IgG N-glycosylation has not been systematically explored. In this review, we delineate the typical immune response to viral infection, expound on the structure and functionality of IgG N-glycans, and summarize the alterations in IgG N-glycans in human serum/plasma post-viral infection, along with the underlying inducements for these modifications. These alterations could serve as biomarkers for viral infectious diseases, thereby facilitating early detection and prognostic assessment of such conditions. Furthermore, exploring these modifications may elucidate the molecular mechanisms underlying the diseases and identify novel therapeutic targets.